Prospective study examining the probability of cerebral fat embolism based on magnetic resonance imaging. Issue 3 (March 2023) - Kanda, Norihide; Miyake, Takahito; Okada, Hideshi; Mizuno, Yosuke; Ichihashi, Masahiro; Kakino, Yoshinori; Fukuta, Tetsuya; Kitagawa, Yuichiro; Yasuda, Ryu; Suzuki, Kodai; Tanahashi, Yukichi; Ando, Tomohiro; et al.
Abstract: Purpose: Cerebral fat embolism (CFE) is a rare syndrome caused by the embolization of fat particles into the brain circulation. This prospective single-center observational study investigated the incidence of CFE in long-bone or pelvic fractures based on magnetic resonance imaging (MRI) findings. The purpose of this study was to investigate the incidence of CFE by MRI findings with or without symptoms suggestive of CFE. Methods: Eligible patients were consecutive, aged 15 years or older, with high-energy traumas, including pelvic or femur fractures. Excluded patients were those who died, could not undergo MRI resulting from medical conditions, or had insufficient mental capacity and no consultee to provide consent. The MRI was scheduled within 4 weeks of the injury, and the images were reviewed by one of the three neuroradiologists who were unaware of the patient's clinical information. Patient data regarding demographics, preceding trauma, injury severity score (ISS), presentation and examination timing of MRI, management including surgery, and outcome were collected. Results: Sixty-two patients were recruited, and three patients were excluded. All patients were injured by blunt trauma. The median patient age was 44 years. The median ISS was 13, and 53 patients needed surgical fixation. There were 22 patients with long-bone fractures, all of whom received external fixation or intramedullary nailing on admission day. MRI was performed after a median hospital day of 18 days. Using MRI imaging, three (5.0%) patients were diagnosed with CFE, and three patients were suspected of CFE. Conclusions: This is the first study to prospectively examine the probability of CFE based on MRI. Since fat embolism syndrome (FES) is confirmed in patients without clinical symptoms, CFE may be more common in patients with trauma than currently believed. Therefore, studies to determine the diagnostic criteria combined with symptoms, MRI, or other objective findings are required in the future. Highlights: CFE is possible in trauma patients with slight mental disturbances, delirium, or even alert patients. CFE is more common in patients with trauma than currently believed. New CFE diagnostic criteria combined with symptoms and other objective findings including MRI are needed.